Pengaruh Literasi Keuangan Syariah terhadap Persepsi dan Minat Menabung Masyarakat Non Muslim pada Bank Syariah - Turahmah, Afifa; Maulana, Zefri; Ula, Tajul (STAI Auliaurrasyidin Tembilahan, 2024)
The interest in saving for non-Muslims is still relatively low in Langsa City due to several influencing factors. This research aims to analyze the influence of sharia financial literacy on the perception and interest in saving of non-Muslim communities at Sharia Banks in Langsa City. The sampling technique in this research used purposive sampling involving 40 respondents. The data analysis method used in this research is Structural Equation Modeling (SEM) with a variance-based approach or component-based structural equation modeling with path analysis. The research results reveal that the variables of Sharia Financial Literacy and perception have a positive effect on Interest in Saving. Apart from that, the perception variable also acts as a mediating variable between the influence of Sharia Financial Literacy on Interest in Saving. The implications of this research reveal that it is important to involve non-Muslims in education programs and sharia financial literacy campaigns to change the non-Muslim community's perception of sharia banks in a positive direction and attract more non-Muslim customers to use sharia banking services.